Kajian Kerusakan Lingkungan Sungai Praigaga Akibat Kegiatan Pertambangan Timah - Balla Nggiku , Umbu Amar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
The change in the profile of the Praigaga River trough around the tin mining of Praimadita Village due to mining is done by three points: the upstream of the river has a width of 6 m and a depth of 120 cm forming the letter "V", while in the middle of the river has a light silting with a width of 4 m and a depth of 60 cm and downstream of the river experiencing more heavy weights, width of 4 m and a depth of 40 cm to form the letter "U". Result of Water Analysis at River Body, Physics and Chemical quality change in Sungai Praigaga which tested in Sukofindo Laboratirium showed that the decreasing quality was on Total Suspended Solid / TSS (deposition) with 14.4 mg / L and Middle 349 mg / L with difference 24.2 mg / L, downstream of 19.2 mg / L, whereas in Total Dissolved Solid / TDS (turbidity) has a difference in the upstream, middle and high downstream even though not exceed the maximum number. The diversity of wildlife species around the tin mining of Praimadita Village, according to the community around the decrease of fish catch, before and after the mining activity, is preceded by the existence of river basins and streams due to mining activities. Public Perceptions of Mining Activity in Preimadita Villages The environmental concerns caused by environmental concerns include land, water, air and forest.